Analysis of The Level of Digitalization of Zakat Management Organizations in Baznas Luwu Raya With The Readiness Index Approach of Zakat Management Organizations - Eva Damayanti; Muh Ruslan Abdullah; Mujahidin (LP2M IAIN Palopo, 2025)
The increasing number of digital information technology users reaching 79.5% in Indonesia in 2024 has great potential to be utilized in helping to increase the realization of ZIS DSKL collection, distribution and reporting activities at BAZNAS institutions digitally. This study aims to analyze, measure and identify the digital readiness of BAZNAS in the Luwu Raya region based on the Digital Readiness Index of Zakat Management Organizations. This study uses a mixed method approach using the MultiStage Weighted Index technique. The subjects of this study were four BAZNAS throughout the Luwu Raya region. There are three dimensions in calculating this index, namely the dimensions of collection, distribution and reporting. Based on the results of the study, it can be seen that there are three BAZNAS that are included in the highest level of readiness category (Digital Native), namely, BAZNAS North Luwu with a value of 0.93; BAZNAS East Luwu with a value of 0.84 and BAZNAS Luwu with a value of 0.81. Meanwhile, BAZNAS Palopo City is at a fairly good level of readiness (IT-Developing) with a value of 0.58. Thus, BAZNAS's digital readiness in Luwu Raya is very good, it only needs to be improved in certain indicators.